Collapse Analysis of Transmission Tower Subjected to Earthquake Ground Motion. (20th February 2018) - Long, Xiaohong; Wang, Wei; Fan, Jian
Abstract : The collapse of transmission towers involves a series of complex problems, including geometric nonlinearity, material nonlinearity, dynamic nonlinearity, and the failure of members. Simulation of the process of collapse is difficult using traditional finite element method (FEM), which is generated from continuum and variation principle, whereas the finite particle method (FPM) enforces equilibrium on each point. Particles are free to separate from one another, which is advantageous in the simulation of the structural collapse. This paper employs the finite particle method (FPM) to simulate the collapse of a transmission steel tower under earthquake ground motions; the three-dimensional (3D) finite particle model using MATLAB and the 3D finite element model using ANSYS of the transmission steel tower are established, respectively. And the static and elastic seismic response analyses indicate that the results of the FPM agree well with those of the FEM. To simulate the collapse of the transmission steel tower, a failure criterion based on the ideal elastic-plastic model and a failure mode are proposed. Finally, the collapse simulation of the transmission steel towers subjected to unidirectional earthquake ground motion and the collapse seismic fragility analysis can be successfully carried out using the finite particle method. The result indicates that the transmission steel tower has better seismic safety performance and anticollapse ability.